SOCIAL MEDIA USAGE AND INTENTION TO INVEST IN SECURITIES CROWDFUNDING IN INDONESIA - Widjaja, Michaelia; Ciawi, Felix; Sekarsari, Dewi; Tamara, Dewi (Ultimaccounting Jurnal Ilmu Akuntansi, 2024)
Abstract— Securities Crowdfunding (SCF) has the potential to grow in Indonesia as it is an alternative investment with calculated risks and consistent returns. However, there is a paucity of research predicting the investment intention of SCF, adding social media usage for informativeness and socializing to investigate further its effect on the intention to invest in SCF by utilizing the Theory of Planned Behavior (TPB). We conducted an online survey to collect the primary data from 200 respondents with financial knowledge and applied the PLS-SEM approach to further test the proposed hypothesis. The results suggest that social media usage for informativeness and socializing contributes to individuals’ perceived behavior control and subjective norms toward the intention to invest in SCF, respectively. This study proved that social media usage for socializing could influence in developing attitude of SCF investing intent. On the contrary, social media for informativeness negatively impacts the attitude toward the intention to invest in SCF. Hence, SCF platforms need to adjust strategies for leveraging social media to increase intention on SCF investment. Understanding these connections is crucial in comprehending how social media impacts financial decision-making processes for potential investors, particularly in the realm of SCF. Keywords: Securities Crowdfunding; Investment Intention; TPB; Social Media Usage; Socializing; Informativeness.